Georgia Architectural and Historic Properties Survey of Rural [027] Middle east section of county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [027] Middle east section of county, Quitman, Ga. December 1980. 1 story rectangular clapboard saddlebag with gabled roof. Square posts surround alcove entrance. Transom and sidelights around doors. Double hung sash windows with 6/6 lights. Set on brick piers. Outbuildings and sheds. Excellent condition. Date of Construction: c. 1900. Typical saddlebag common to this area.
Georgia Architectural and Historic Properties Survey of Rural [027] Middle east section of county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.28 MB (1,350,005 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Ousley (Ga.)